The Hegemonic Domination of English over Bangla in Bangladeshi English Medium Contexts - Haque, Arpita (Journal of NELTA, 2020)
The paper reports on a study which investigated the status of English and Bangla among the English medium (EM) school students in Bangladesh. The main objectives of this study were to find out the attitudes of the English medium (EM) students and their parents towards Bangla and English language and culture, and to identify to which language and culture the students are most frequently exposed. The study also aimed at addressing the issue of hegemony related to English and Bangla language and culture. This study was based on a questionnaire survey. The participants in this study were 65 EM students and 23 parents. The results revealed that the students had highly favourable attitudes towards the English language and culture. Their attitudes towards Bangla were not negative but their responses about their cultural and recreational involvement showed that they were highly exposed to the English language and culture, not to Bangla. These in conjunction with the parents’ responses indicated that there is a potential linguistic and cultural hegemony at work for which the students are facing distancing from Bangla language and culture in favour of the English ones.